Modern metallography – the basis of foundry material science - A. G. Anisovich (Литьë и металлургия)
The article briefly discusses the capebilities of modern metallography – optical contrasting, quantitative metallography, image processing programs. The question of the absence of modern literature on metallography is touched on. The problem of representing the structures of materials and the Internet is discussed. The problems of the development of metallographic research in Belarus are also presented. It is noted that the development of metallographic research in Belarus is hampered by the lack of funds for the acquisition of the equipment, as well as the lack of qualified personnel.